Optimization of the casting process from environmentally friendly bentonite-based sand for efficient casting during melting in an electric arc furnace (Eurasian Journal of Engineering and Technology, 2023)
Foundry production is one of the most diverse industries. In the foundry, several methods are used to manufacture a part. It includes processes such as centrifugal casting, permanent casting, die casting and sand casting. The article presents the process of casting into sand molds with bentonite. In the article, the authors conducted comparative studies of the reduction of marriages by porosity. In the course of the experiments, relevant analyses and conclusions are presented.